Construction of top university identity in high-stakes genres of public communication – a systemic functional discourse analysis of three genres of PKU and THU presidential talk and letter to prospective students. (4th May 2020) - Tian, Jianqiu
ABSTRACT: This article highlights the pivotal role of genre in text production and identity construction by an analysis of three high-stakes genres of public communication by presidents of the top universities in China, Peking University (PKU) and Tsinghua University (THU). A brief review of the Systemic Functional Linguistic (SFL) research on identity indicates that the current approach did not take into account the role of text structure as an important means of identity construction, which can be attributed to flaws in the SFL theorization of genre. In view of this, the Genre as a Nexus of meaning making (GaN) model is proposed, followed by a reinforced analytical framework of text analysis encompassing Halliday (and Matthiessen)'s functional grammar and Martin (and Rose)'s discourse semantics, which is subsequently deployed to study the texts of concern from an SFL vantage point. The results indicate that not only are different aspects of the university represented in the different genres, but the generic structure of the texts is indispensable in the university's identity construction. Moreover, the comparison of the genres with those in other culture and of the results with previous research underscores culture's powerful impact on genre and the universities at the forefront of globalization.